Recent Progress in the Consistent Interpretation of Complementary Spectroscopic Results Obtained on Molecular Systems. Issue 14 (10th May 2021) - Forker, Roman; Gruenewald, Marco; Kirchhuebel, Tino; Fritz, Torsten
Abstract: Research on organic thin films is largely driven by potential (opto‐)electronic applications and turns out to be no less intriguing from a fundamental point of view. Numerous studies make it clear that the understanding of device‐relevant molecular thin film architectures is quite challenging—often hampered by insufficient spectroscopic data and the lack of a consistent interpretation of the available datasets. Consequently, speculative aspects prevail in the discussion of energy levels in conjunction with the optical properties of organic thin films. Adequate spectroscopic techniques applicable to thin films of organic molecules (typical thicknesses required for devices are in the nanometer range) with the necessary sensitivities are rather demanding. Some of those methods were developed or significantly improved in the recent past. Here, the now available complementary spectroscopies are briefly surveyed with particular emphasis on some techniques that have not yet become widespread standards, and a non‐exhaustive set of examples of acquired experimental results are provided. For a consistent interpretation of the latter, the concepts brought forward in the literature considering the role of initial and final states of spectroscopic processes are outlined, with important consequences for quantitatively correct energy diagrams. Abstract : Surface‐sensitive spectroscopic techniques applied to thin organic films are briefly surveyed. A model is presented that explicitly takes the initial and final states of the probe processes into account. On the basis of charging energies, the measurement perturbations can be understood for molecules in the gas phase and adsorbed on a surface, which ultimately yields quantitatively accurate energy diagrams.